2011
DOI: 10.1371/journal.pone.0019738
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Inexpensive Device for Nucleic Acid Amplification without Electricity—Toward Instrument-Free Molecular Diagnostics in Low-Resource Settings

Abstract: BackgroundMolecular assays targeted to nucleic acid (NA) markers are becoming increasingly important to medical diagnostics. However, these are typically confined to wealthy, developed countries; or, to the national reference laboratories of developing-world countries. There are many infectious diseases that are endemic in low-resource settings (LRS) where the lack of simple, instrument-free, NA diagnostic tests is a critical barrier to timely treatment. One of the primary barriers to the practicality and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 38 publications
(44 reference statements)
0
130
0
Order By: Relevance
“…While DNA detection technology implementation is costly and technically challenging in many countries with limited resources, recent technology has been reported that may facilitate the performance of these assays in areas with inadequate or absent freezing conditions (our unpublished results) or even in areas with no electric power [11]. Information obtained on intestinal E. coli pathogens through these assays is the basis for the epidemiological surveillance information on which national and international public health authorities depend to implement preventive measures, recommend pathogen-specific medical management, and invest in vaccine development research.…”
Section: Introductionmentioning
confidence: 87%
“…While DNA detection technology implementation is costly and technically challenging in many countries with limited resources, recent technology has been reported that may facilitate the performance of these assays in areas with inadequate or absent freezing conditions (our unpublished results) or even in areas with no electric power [11]. Information obtained on intestinal E. coli pathogens through these assays is the basis for the epidemiological surveillance information on which national and international public health authorities depend to implement preventive measures, recommend pathogen-specific medical management, and invest in vaccine development research.…”
Section: Introductionmentioning
confidence: 87%
“…Bst 2.0 DNA polymerase, 10× Isothermal Amplification Buffer, dNTPs, DNA/DNase-free stocks of MgSO 4 , and restriction endonucleases were purchased from New England Biolabs (Ipswich, MA), and betaine was from Sigma-Aldrich (St. Louis, MO). Pooled human plasma in sodium heparin derived from whole blood donations was acquired from Valley Biomedical Products and Services, Inc. (Winchester, VA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…188 Conversely, many efforts are addressing suitable methodology and technology for wider and, importantly, more affordable use of RQ-PCR. 189 Another important test in molecular monitoring of CML patients is BCR-ABL1 kinase domain mutation analysis in those who have acquired TKI resistance and who might require an alternative treatment, or those who progress to advanced phase disease. This test also helps to determine the clinical consequences of clonal diversity of BCR-ABL1 and the co-existence of subclones.…”
Section: -177mentioning
confidence: 99%